PELATIHAN SISKEUDES PERWUJUDAN EFEKTIVITAS PEMERINTAH DESA DI KECAMATAN JATIPURNO - Fajarwati Kusuma Adi; Ana Baroroh (Jurnal Al Basirah, 2021)
Siskeudes training is a facility carried out by the village government in Jatipurno District which aims to increase understanding of village skills related to village financial management which are still low so that village operators who are skilled in the village financial system are needed. This is based on Law No. 6 of 2014 concerning Villages as stated in Article 1 paragraph (2) that village government is the administration of government affairs and the interests of the community, while paragraph (3) explains that what is meant by Village Government is a government consisting of on the Village Head with the assistance of village officials who are referred to as elements of village government administration. The method used in this service is a qualitative method and is supported by laws, books, journals and the internet. By taking samples for the implementation of activities, the training participants and interviews with village officials, namely: village head planning and treasurer The training that the author provides has implications in the form of APBDes budgeting input followed by input of all transactions in and out of money in administration , providing training and mentoring materials, namely the Siskeudes Application.